L’immobilier residentiel : principal moteur de la fabrique urbaine de Ho Chi Minh Ville - Clément Musil; Danielle Labbé; Vu Ngoc Khanh (EchoGéo)
Using the case of the district 2 and Thủ Thiêm New Urban Area, this article explores the growing importance of private property developers in Ho Chi Minh City and its effects on the production of new urban territories. While the residential property market of Ho Chi Minh City is among the most dynamic in Southeast Asia, the local government relies on private developers and investors to produce the infrastructure needed by the metropolis and to ensure its economic and territorial growth. Despite existing safeguards, official rules and regulations are bypassed, contributing to the dilapidation of public assets meant to finance the ongoing urbanization.